A Horizontal Magnetic Tweezers for Studying Single DNA Molecules and DNA-Binding Proteins - Roberto Fabian; Santosh Gaire; Christopher Tyson; Raghabendra Adhikari; Ian Pegg; Abhijit Sarkar (Molecules, 2021)
We report data from single molecule studies on the interaction between single DNA molecules and core histones using custom-designed horizontal magnetic tweezers. The DNA-core histone complexes were formed using λ-DNA tethers, core histones, and NAP1 and were exposed to forces ranging from ~2 pN to ~74 pN. During the assembly events, we observed the length of the DNA decrease in approximate integer multiples of ~50 nm, suggesting the binding of the histone octamers to the DNA tether. During the mechanically induced disassembly events, we observed disruption lengths in approximate integer multiples of ~50 nm, suggesting the unbinding of one or more octamers from the DNA tether. We also observed histone octamer unbinding events at forces as low as ~2 pN. Our horizontal magnetic tweezers yielded high-resolution, low-noise data on force-mediated DNA-core histone assembly and disassembly processes.